Effect of MgO shell on electron transfer from Cu doped ZnInS quantum dots to FePt nanoparticles. (July 2018) - Liu, Yang; Hua, Jie; Zhang, Kewei; Zhao, Jialong; Li, Haibo
Graphical abstract: The formation of interfacial MgO barriers could efficiently restrain the electron transfer at Cu doped ZnInS QD-FePt NP interface. Highlights: MgO-coated FePt NPs were synthesized using 4 nm FePt cores as seeds for the growth of MgO shell. Significant PL quenching took place in Cu doped ZnInS QD-FePt NP system owing to photoexcited electron transfer. The formation of interfacial MgO barriers could efficiently restrain the electron transfer at QD-FePt interface. Abstract: The effect of MgO shell on the electron transfer between luminescent Cu doped ZnInS quantum dots (QDs) and magnetic FePt/MgO core/shell nanoparticles (NPs) was studied by using steady-state and time-resolved photoluminescence (PL) spectroscopy. MgO-coated FePt NPs were synthesized using 4 nm FePt cores as seeds for the growth of MgO shell, having a reduced saturation magnetization M s compared to the pure FePt NPs. It was found that the shortening in PL lifetime of Cu doped ZnInS QDs induced by FePt NPs demonstrated an electrons transfer process from excited QDs to the adjacent FePt NPs. When FePt NPs were coated with a MgO shell, the low work function of MgO shell resulted in a formation of higher interfacial barriers between Cu doped ZnInS QDs and FePt NPs, significantly suppressing the electron transfer at Cu doped ZnInS QD-FePt NP interface.